2006
DOI: 10.2136/vzj2005.0002
|View full text |Cite
|
Sign up to set email alerts
|

Borehole Environmental Tracers for Evaluating Net Infiltration and Recharge through Desert Bedrock

Abstract: Permeable bedrock aquifers in arid regions are being increasingly developed as water supplies, yet little is generally known about recharge processes and spatial and temporal variability. Environmental tracers from boreholes were used in this study to investigate net infiltration and recharge to the fractured Navajo Sandstone aquifer. Vadose zone tracer profiles at the Sand Hollow study site in southwestern Utah look similar to those of desert soils at other sites, indicating the predominance of matrix flow. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 46 publications
2
28
0
Order By: Relevance
“…It is assumed therefore that the Sc values of the excavations represent peak concentrations of solute accumulation. Net infiltration rates determined previously by using the vadose zone 3 H depth-to-peak method [Cook et al, 1994] ranged from 2 to more than 57 mm/yr at 11 borehole locations in Sand Hollow [Heilweil et al, 2006] (Figure 3). Dividing the recharge rate at each location by the precipitation rate yields the average annual net infiltration ratio.…”
Section: Net Infiltration Estimates Along Excavationsmentioning
confidence: 79%
See 2 more Smart Citations
“…It is assumed therefore that the Sc values of the excavations represent peak concentrations of solute accumulation. Net infiltration rates determined previously by using the vadose zone 3 H depth-to-peak method [Cook et al, 1994] ranged from 2 to more than 57 mm/yr at 11 borehole locations in Sand Hollow [Heilweil et al, 2006] (Figure 3). Dividing the recharge rate at each location by the precipitation rate yields the average annual net infiltration ratio.…”
Section: Net Infiltration Estimates Along Excavationsmentioning
confidence: 79%
“…Although the spatial distribution of the GIS-predicted rates is based on vadose zone solutes (Cl, Sc), net infiltration values are determined by correlations between solute accumulation and borehole vadose zone 3 H using the depth-to-peak method rather than the Cl mass balance method. This approach was designed to take advantage of the much larger data set of solute concentrations along the 3350 m of excavations for describing the relative spatial variability in net infiltration, yet the more precise rates (±50%), primarily because of uncertainty in atmospheric Cl deposition rates, and (3) 3 H-based net infiltration rates at high-recharge borehole sites in Sand Hollow more closely correspond to groundwater Cl-based estimates than rates based on vadose zone Cl [Heilweil et al, 2006]. In this previous work, recharge rates determined with the CMB method using water table Cl concentrations were compared to net infiltration rates determined from vadose zone borehole environmental tracers using (1) the CMB method with Cl from the soil/bedrock interface to the bottom of the Cl bulge, (2) the CMB method with Cl from the bottom of the bulge to the water table, (3) the 3 H depth-to-peak method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recharge rates range from 2 to 57 mm year 1 according to unsaturated zone tritium data, and from 0Ð5 to 13 mm year 1 according to unsaturated zone chloride data beneath the bulge. Recharge rates based on saturated zone Scanlon et al, 2005a) chloride concentrations are similar (mean ¾11 mm year 1 , ¾5% of precipitation, range 3-60 mm year 1 ) (Appendices I, II; Table I; Heilweil et al, 2006). Noble gases and tritium-helium dating in the saturated zone were used to estimate recharge in eastern Salt Lake Valley in northern Utah (Manning and Solomon, 2004 adjacent Wasatch Mountains represents ½30% and more likely 50 to 100% of recharge throughout the basin.…”
Section: United Statesmentioning
confidence: 99%
“…Studies have been conducted in Argentina in areas where pampas grasslands have been replaced by eucalyptus plantations Figure 12. Relationship between recharge and precipitation from studies of large natural areas 40-374 200 km 2 using methods that reflect regional recharge rates (modelling, saturated zone CMB, micro-gravity, and water-table fluctuations) (Leaney and Allison, 1986;Edmunds et al, 1988;Bazuhair and Wood, 1996;Sami and Hughes, 1996;de Vries et al, 2000;Love et al, 2000;Anderholm, 2001;Leduc et al, 2001;Flint et al, 2002Flint et al, , 2004Favreau et al, 2002b;Harrington et al, 2002;Hevesi et al, 2003;Goodrich et al, 2004;Sanford et al, 2004;Heilweil et al, 2006;Keese et al, 2005) Copyright (Jobbagy and Jackson, 2004). Detailed studies of the impact of a 40-ha eucalyptus plantation on groundwater over 2 years indicated that groundwater discharged more than 50% of the days through ET depressing the water table by >0Ð5 m and increasing groundwater salinity by factors of 2-19, depending on soil texture (Jobbagy and Jackson, 2004;Engel et al, 2005).…”
Section: Impact Of Land Use/land Cover Change On Rechargementioning
confidence: 99%